Non-parametric Stability Analysis in Durum Wheat (Triticum durum Desf.) Genotypes Growing under Semi-arid Conditions - Guendouz, Ali; Boucherb, Radia (International Journal of Bio-resource and Stress Management, 2022)
Field experiments were carried out in National Institute of Agronomic Research of Algeria INRAA- station of Setif, Algeria where grain yield of 10 durum wheat genotypes tested during 4 cropping seasons from 2009 to 2013 and sowing in the same period in December .The objectives were to determine stable genotypes based on non-parametric stability indices. The results of the Thennarasu (NP) as following: Si(1) (varied from 2 to 5), Si(2) (varied from 3 to 17), Si(3) (varied from 1.2 to 9.27) and Si(6) (varied from 0.67 to 2.55) based on these methods the genotype Mexicali75is considered to be most stable and had highest grain yield. Based on NP1, NP3 and NP4 the genotype Mexicali75is considered to be most stable and had highest grain yield, the genotype Hoggar had low values for the index NP2 we can considered more stable but with moderate grain yield. In addition, the results of the methods of Huehn demonstrate that the genotype Mexicali75 with the lowest values was identified as desirable. The results of Spearman’s rank correlation coefficients between mean yield and the non-parametric stability statistics are shown in Table 4. The mean grain yield as well as negatively and significantly correlated with NP2, NP3 and NP4 and insignificant negative correlation with NP1. In conclusion, according to results of these different non-parametric stability measurements, genotype Mexicali75 is recommended for commercial release as a favorable durum wheat genotype for the semi-arid condition.